Enhanced capacitance of phosphorus, nitrogen, and oxygen tri-doped balsa wood-based porous carbon for supercapacitors. (February 2023) - Luo, Lingcong; Lan, Yuling; Zhang, Qianqian; Deng, Jianping; Zeng, Qinzhi; Gao, Haili; Du, Guanben; Zhao, Weigang
Abstract: Porous activated carbons derived from ultra-low density biomass of balsa wood are prepared by a one-step phosphoric acid activation method under different impregnation ratios without using dopants or post-treatments. These carbon materials are investigated and evaluated in terms of their morphology, texture structure, surface properties, chemical properties, and physical properties, as well as their electrochemical performance. The results indicate that the prepared phosphorus, nitrogen, and oxygen tri-doped balsa activated Carbons (PNOACs) exhibited hierarchical pore structures (micro-, meso-, and macropores). The surface area, pore size distribution, and also the heteroatoms (P/N/O) content of balsa wood active materials can be effectively controlled by the phosphoric acid activation process. Using PNOAC600-2, the active material electrode in the three-electrode system possesses a maximum specific capacitance of 263 F g −1 at 0.5 A g −1 . The corresponding specific surface area and total pore volume are 1191.65 m 2  g −1 and 1.19 cm 3 /g, respectively; while the heteroatom contents of nitrogen, phosphorus, and oxygen are 0.62, 3.43 %, and 15 %, respectively. Both the hierarchical pore structures and the heteroatoms have great influence and contribution to the specific capacitance performance. The assembled symmetric supercapacitor also exhibits a good capacitance retention rate (91.48 %), long-term charge/discharge cycling stability, and energy density (9.2 Wh kg −1 ). Using the one-step phosphoric acid activation method, a new method for developing and utilizing high-value balsa wood in the field of electrochemical energy storage is provided. Graphical abstract: Unlabelled Image Highlights: Heteroatoms P, N, and O have been successfully incorporated in the carbon framework. P, N, and O tri-doped ACs were synthesized by one-step preparation from balsa wood. High capacitance of 263 F g −1 at 0.5 A/g was obtained by PNOACs. An assembled symmetric supercapacitor shows a high energy density of 9.2 W h/kg.